EUS-guided gallbladder drainage in patients with cirrhosis: results of a multicenter retrospective study - James, Theodore W.; Krafft, Matthew; Croglio, Michael; Nasr, John; Baron, Todd (Endoscopy International Open, 2019)
Background and study aims Cirrhosis has historically been considered a relative, if not absolute, contraindication to cholecystectomy. Endoscopic ultrasound-guided gallbladder drainage (EUS-GBD) has been developed for use in non-operative candidates with cholecystitis; however, little data exist for use of the procedure in patients with cirrhosis.Patients and methods This was a retrospective series involving two large tertiary referral centers performing EUS-GBD. Patients with cirrhosis who underwent EUS-GBD for cholecystitis between August 2014 and December 2018 were identified. The primary endpoint was the rate of technical success, defined as EUS-guided placement of a lumen-apposing metal stent (LAMS) from duodenum to gallbladder. Patient demographics, procedural details, adverse events (AEs), post-procedural symptoms, and clinical success were recorded.Results Fifteen patients (9 females, 6 males) with cirrhosis underwent EUS-GBD during the study period. Mean patient age was 61 ± 17.1yrs, mean MELD-Na 15 ± 7. Etiology of cirrhosis was HCV (n = 2), alcohol (n = 4), non-alcoholic fatty liver disease (n = 8), and autoimmune hepatitis (n = 1).The technical success rate was 93.3 % and mean procedure time was 64 ± 59 minutes. Initial puncture site was duodenum (n = 11), stomach (n = 3) and jejunum (n = 1) and portion of gallbladder used for drainage was neck (n = 4) and body (n = 11). Fourteen patients went on to clinical success and two AEs occurred in this cohort. One decompensation event occurred in a patient with Child-Pugh class C disease 3 weeks post-procedure. Mean length of follow-up was 373 ± 367.3 days; one death occurred due to underlying malignancy.Conclusion EUS-GBD is safe and efficacious in managing cholecystitis in patients with Child-Pugh A and B cirrhosis who are non-operative candidates. Further studies are needed to determine optimal patient selection and procedural technique.